Refining the identification criteria for forma typica and brachycerca in exuviae of Boyeria irene (Odonata: Aeshnidae) - Nunes, L.F. (2022)
In female imagines of Boyeria irene, two forms are known according to the length of the cerci: forma brachycerca (short appendages) and f. typica (long appendages). Both forms are also recognisable in exuviae. Hitherto, no accurate measurements have been performed to distinguish between the two forms. Hence, we measured and analysed the absolute and relative length of the cerci in both sexes of exuviae from 11 populations originating from the centre and north of the Iberian Peninsula. We show that there are specimens intermediate between the two forms and that dimorphism is also present in males. The brachycerca form is more frequent in the north than in the centre of the Iberian Peninsula. Correct identification of both forms should always be based on accurate measurements of the length of the cerci.